Oral flora in acute stroke patients: A prospective exploratory observational study. (22nd May 2017) - Boaden, Elizabeth; Lyons, Mary; Singhrao, Sim K.; Dickinson, Hazel; Leathley, Michael; Lightbody, Catherine E.; McLoughlin, Alison; Khan, Zarine; Crean, Stjohn; Smith, Craig; Higham, Susan; Watkins, Caroline
Abstract : Objective: To describe the bacterial profile of the oral flora during the first 2 weeks following a stroke, examining changes in the condition of the oral cavity and infections. Background: Dysphagia is common after a stroke and can lead to aspiration pneumonia. Oral flora changes associated with stroke have been implicated as a possible source of bacteria that can cause systemic infections. Materials and methods: Seventy‐seven participants were recruited over a period of 9 months. Fifty participants had a complete set of swabs from four different oral sites and a saliva sample taken at three time points over a 14‐day period. Molecular identification of bacteria was performed on the pooled DNA extracted. Results: A total of 103 bacterial phylotypes were identified, 29 of which were not in the Human Oral Microbiome Database (HOMD). Fourteen of the twenty most common bacterial phylotypes found in the oral cavity were Streptococcal species with Streptococcus salivarius being the most common. The condition of the oral cavity worsened during the study period. Fifteen (30%) patients had at least one infection. Conclusions: There appears to be huge diversity of bacterial organisms in the oral cavity of stroke patients, and as most phylotypes identified were only found in one or two participants, no particular patterns linked to infection or the condition of the oral cavity could be discerned.